Implementation of Techniques for Fault Tolerance in a Network-on-Chip - Veiga, Fabricio; Zeferino, Cesar Albenes (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2010: Anais do XI Simpósio em Sistemas Computacionais de Alto Desempenho, 2010)
Networks-on-Chip (NoCs - Networks-on-Chip) have emerged as the best alternative to provide high performance in communication for futures Systems-on- Chip (SoCs) with dozens of cores integrated on a single silicon die. However, the components of a NoC are susceptible to faults resulting from heating, power surge, external radiation and others. Faults in a router or a network link can lead to the transfer of erroneous data or, depending on the nature of the fault, cause problems in routing packets, such as forwarding a packet to an incorrect destination or even prevention of a particular path network is used, resulting in system failures. A fault tolerant NoC should be able to detect a fault and prevent it from leading to a system failure, ensuring the correct operation of the application. This paper presents the implementation of techniques for detection and recovery of faults in a NoC, which were modeled in SystemC and validated by simulation. Results compare the effectiveness of two techniques to provide fault tolerance to a NoC.